Aestivation motifs explain hypertension and muscle mass loss in mice with psoriatic skin barrier defect - Wild, Johannes; Jung, Rebecca; Knopp, Tanja; Efentakis, Panagiotis; Benaki, Dimitra; Grill, Alexandra; Wegner, Joanna; Molitor, Michael; Garlapati, Venkata; Rakova, Natalia; Markó, Lajos; Marton, Adriana; et al. (Acta Physiologica, 2021)
Aim: Recent evidence suggests that arterial hypertension could be alternatively explained as a physiological adaptation response to water shortage, termed aestivation, which relies on complex multi-organ metabolic adjustments to prevent dehydration. Here, we tested the hypothesis that chronic water loss across diseased skin leads to similar adaptive water conservation responses as observed in experimental renal failure or high salt diet. Methods: We studied mice with keratinocyte-specific overexpression of IL-17A which develop severe psoriasis-like skin disease. We measured transepidermal water loss and solute and water excretion in the urine. We quantified glomerular filtration rate (GFR) by intravital microscopy, and energy and nitrogen pathways by metabolomics. We measured skin blood flow and transepidermal water loss (TEWL) in conjunction with renal resistive indices and arterial blood pressure. Results: Psoriatic animals lost large amounts of water across their defective cutaneous epithelial barrier. Metabolic adaptive water conservation included mobilization of nitrogen and energy from muscle to increase organic osmolyte production, solute-driven maximal anti-diuresis at normal GFR, increased metanephrine and angiotensin 2 levels, and cutaneous vasoconstriction to limit TEWL. Heat exposure led to cutaneous vasodilation and blood pressure normalization without parallel changes in renal resistive index, albeit at the expense of further increased TEWL. Conclusion: Severe cutaneous water loss predisposes psoriatic mice to lethal dehydration. In response to this dehydration stress, the mice activate aestivation-like water conservation motifs to maintain their body hydration status. The circulatory water conservation response explains their arterial hypertension. The nitrogen-dependency of the metabolic water conservation response explains their catabolic muscle wasting.
CRIS-Team Scopus Importer:2021-03-05
Keywords: aestivation; catabolism; dehydration; double barrier concept; hypertension; transepidermal water loss